KONSEP SABAR DALAM PERSPEKTIF AL–GHAZALI DAN IMPLEMENTASINYA PADA MASA PANDEMI COVID-19 - Hensa Ilham Intan Lutfi Primalita; Alfina Hidayah (Academic Journal of Islamic Principles and Philosophy, 2021)
The Covid-19 pandemic is an extraordinary event that is happening right now with various accompanying impacts, especially for the mental and spiritual condition of humans. Therefore, patience is one of attitudes and characters that must be owned by anyone, because it is believed that by being patient at least able to strengthen a person in the face of a pandemic situation. In Islam, patience is a noble character taught especially by Sūfīs like Al-Ghazali, thus this research was conducted to find out the concept of patience according to Al-Ghazali which includes the meaning of patience, the virtue of patience and its implementation in human life during the Covid-19 Pandemic. This type of research is a literature study with a descriptive analysis method. The conclusions of this study included the way s for having a patient nature according to al-Ghazali are by weakening the drive for lust and strengthening the driving force of religion. Patience in human life has implications for religious life and social life, so patience has the potential to make one's religious and social life better.